well if your sum is -18 then you know your answers are going to be negative numbers.
make x be your first unknown negative even integer. you want your negative x and then negative x minus two and negative x minus four
x1= x
x2= x-2
x3= x-4
you know all three need to equal -18
solve for x:
-18= -x + (-x-2) + (-x-4)
-18 = -x-x-2-x-4
-18+2+4= -3x
12=-3x
12/-3=x
-4=x
then plus x into the first problem.
x1= -4 = -4
x2= -4-2 = -6
x3= -4-4 = -8
so your integers would be -4, -6, and -8
check:
(-4) + (-6) + (-8) = -18
let me know if you have any questions.